Portugal finissecular nas crônicas de D. João da Câmara publicadas na revista portuguesa O Ocidente e no jornal brasileiro Gazeta de Notícias (1901-1905) - Araújo, Rita de Cássia Lamino [UNESP] (2015)
In the end of the XIX century and beginning of the XX, Portugal was going through a moment of politics and economic crises and also the stagnancy of the cultural life. In the face of this situation, while members of the Portuguese elite, residents of the big centers, especially in Lisbon, lived under the illusion of a modern and cosmopolitan life, the Portuguese worker, especially the peasant emigrated to Brazil, trying to find better life conditions. In Rio de Janeiro, the Portuguese immigrant found a progressive society which contributed and was very good to his development. In his context, it is found the chronicles of D. João da Câmara disclosed, at the same time, from 1901 to 1905, in the Portuguese release O Ocidente: Revista Ilustrada de Portugal and of the Estrangeiro and in the Brazilian newspaper Gazeta de Notícias, that constitute the corpus of this thesis. Before this confirmation, this research has as an aim to demonstrate the way how D. João da Câmara absorbed Portugal in the end of century and the crisis which it was going through and transmitted to the readers from different social contexts. From one side, the Portuguese, the one that lives in Lisbon near the problems of his country, and from the other, the Brazilian reader, in special, the Portuguese immigrant who misses his hometown. On the analysis methodology, it was intended to observe the thematic and the style of the chronic considering the social moment, the way of disclosure and the reader. As a conclusion for the research, it can be noticed that both the journals D. João da Câmara facing Portugal of the end of the century, sometimes presents the problems of the country and how miserable he felt about it, and other times lets his aristocratic ideas appear relying on the power of recovery of the old Portuguese nation, above all, by the valuation of the countryside, the glorious history and the Portuguese traditions...